Performance evaluation of utilization of waste Polyethylene Terephthalate (PET) in stone mastic asphalt - Ahmadinia, E.; Zargar, M.; Karim, Mohamed Rehan; Abdelaziz, M.; Ahmadinia, E. (Elsevier, 2012)
In order to improve the properties of asphalt mixture and reduce the negative impact of the waste materials on nature and the environment, it seems to be logical to propose a means of re-using waste materials in engineering and industrial construction projects such as road pavement. The current paper presents an experimental research on the application of waste plastic bottles (Polyethylene Terephthalate (PET)) as an additive in stone mastic asphalt (SMA). Wheel tracking, moisture susceptibility, resilient modulus and drain down tests were carried out on the mixtures that included various percentages of waste PET as 0, 2, 4, 6, 8 and 10 by weight of bitumen content. By experimentation, the appropriate range for the amount of waste PET was determined to be 4-6 by weight of the bitumen content. The results show that the addition of waste PET into the mixture has a significant positive effect on the properties of SMA which could improve the mixture's resistance against permanent deformation (rutting), increase the stiffness of the mix, provide lower binder drain down and promotion of re-use and recycling of waste materials in a more environmentally and economical way.